A Magnetic Resonance-Relaxometry-Based Technique to Identify Blood Products in Brain Parenchyma: An Experimental Study on a Rabbit Model - Del Signore, Francesca; Vignoli, Massimo; Della Salda, Leonardo; Tamburro, Roberto; Paolini, Andrea; Cerasoli, Ilaria; Chincarini, Matteo; Rossi, Emanuela; Ferri, Nicola; Romanucci, Mariarita; Falerno, Ilaria; de Pasquale, Francesco (Frontiers in Veterinary Science, 2022)
Magnetic Resonance relaxometry is a quantitative technique that estimates T1/T2 tissue relaxation times. This has been proved to increase MRI diagnostic accuracy of brain disorders in human medicine. However, literature in the veterinary field is scarce. In this work, a T1 and T2 based relaxometry approach has been developed. The aim is to investigate its performance in characterizing subtle brain lesions obtained with autologous blood injections in rabbits. This study was performed with a low-field scanner, typically present in veterinary clinics. The approach consisted in a semiautomatic hierarchical classification of different regions, selected from a T2 map. The classification was driven according to the relaxometry properties extracted from a set of regions selected by the radiologist to compare the suspected lesion with the healthy parenchyma. Histopathological analyses were performed to estimate the performance of the proposed classifier through Receiver operating characteristic curves analyses. The classifier resulted moderately accurate in terms of lesion characterization.